2011
DOI: 10.1097/pec.0b013e318222554e
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability of Mental Health Screening in a Pediatric Emergency Department

Abstract: Overall, mental health screening appears to be acceptable in the pediatric ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 26 publications
2
33
3
1
Order By: Relevance
“…Several studies reported a marked increase in the number of children and adolescents seeking care for mental health problems in emergency settings (10)(11)(12)(13)(14)(15). Also, the prevalence of mental health problems in pediatric EDs has been found to be much higher (1). Therefore, pediatric EDs have become a primary point of screening and/or evaluation of mental health problems, regardless of whether the problems are considered to be true mental health emergencies (12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported a marked increase in the number of children and adolescents seeking care for mental health problems in emergency settings (10)(11)(12)(13)(14)(15). Also, the prevalence of mental health problems in pediatric EDs has been found to be much higher (1). Therefore, pediatric EDs have become a primary point of screening and/or evaluation of mental health problems, regardless of whether the problems are considered to be true mental health emergencies (12).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 7%-22% of youth in nonclinical settings have a mental illness (1). The identification of mental disorders in primary care settings have increased rapidly in the recent 2 decades (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teenagers and parents both report favorable attitudes toward mental health screening during an ED visit. 153,154 In this study, suicide and drug and alcohol screening rated as more important than other mental health problems. Female adolescents and their parents, more than male adolescents, expressed positive views on screening.…”
Section: Feasibility and Acceptability Of Ed Mental Health Screeningmentioning
confidence: 98%
“…Perceived and real barriers to such screening exist, including lack of training, time constraints, and increasing ED patients' length of stay. Williams et al 154 investigated this question and found that 99% of physicians and 97% of nurses stated that a brief, validated screening tool did not interfere with patient care. In addition, research staff endorsed "no difficulty" in administering the screen to 73% of participants.…”
Section: Feasibility and Acceptability Of Ed Mental Health Screeningmentioning
confidence: 99%